Clinical Demands and Nursing Interventions in Gerontological Consultations: An Integrative Review - Muniz, Vinícius de Oliveira (2024)
Introduction: The creation of guidelines that unify the prevalent clinical demands from gerontological nursing consultations and their corresponding interventions are necessary due to the heterogeneity of emerging pathologies in the aging process that will require nursing care. Objective: To identify clinical demands in gerontological nursing consultations and the interventions implemented by nurses. Method: An integrative review of original research published from 2018 and 2022, in English, Spanish, and Portuguese, in Scopus, MEDLINE/PubMed, BIREME/lilacs/BDENF/IBECS/VHL, SciELO, and Google Scholar databases, using the DeCS/MESH descriptors: "Elderly", "Nursing in the Office", "Geriatric Nursing", and "Geriatrics". The Rating System for the Hierarchy of Evidence for Intervention was used to determine the level of evidence of the final sample. Editorials, review studies, and duplicate articles were excluded. The data were analyzed by analytical and interpretative reading, guided by a checklist. Results: Eight articles were selected that showed clinical demands such as deficits in self-care for bathing, self-negligence, fatigue, risk of damaged skin integrity, hopelessness, sadness, and depression. Interventions were related to encouraging self-care, medication optimization, encouragement of exercise, skin care, counseling, music therapy, and psychosocial rehabilitation. Conclusion: There are many different clinical demands in gerontological nursing consultations, especially associated with the domain of activity/rest. These include interventions to treat and prevent diseases, and actions aimed at health promotion, in most cases associated with the Behavioral domain.